Criminal Aspects Of The Fiduciary Guarantee Transfer As Decision Basis On Criminal Justice Process - Suwanto Suwanto; Sri Kusriyah Kusriyah; Bambang Tri Bawono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The research problems are: What is the criminal aspect to the transfer that occurred on fiduciary as the basis for the decision in the court proceedings? The approach used in this research is normative juridical approach or the written law (law/statute approach), This approach is also known by the literature approach, namely by studying books-books, legislation and other documents related to this research. The study concluded that the diversion of the object fiduciary by the debtor without the consent from creditors including activities that violate the rights of creditors as the recipient of fiduciary protected by the Fiduciary Law, specifically Article 36 of Act No. 42 Of 1999 On Fiduciary.Keywords: Criminal Aspects; Fiduciary Guarantee Transfer; Criminal Justice.